Baseline thrombocytopenia in acute coronary syndrome: The lower, the worse. (1st June 2021) - Chao, Chieh-Ju; Shanbhag, Anusha; Chiang, Chia-Chun; Girardo, Marlene E.; Seri, Amith R.; Khalid, Muhammad U.; Rayfield, Corbin; O'Shea, Michael P.; Fatunde, Olubadewa; Fortuin, F. David
Abstract: Background: Patients with baseline thrombocytopenia can have increased mortality and morbidity, but are typically excluded from randomized clinical trials studying acute coronary syndromes (ACS). We sought to better define the effect thrombocytopenia on clinical outcomes in ACS patients. Methods: Patients identified from the NCDR Chest Pain registry at Mayo Clinic Arizona from Oct 2015 to Sep 2018 were retrospectively classified into two groups: TP (platelet <150 × 10 3 μL) and control (platelet ≥150 × 10 3 μL). The groups were analyzed for the clinical outcome (all-cause mortality, major adverse cardiac events (MACE), and bleeding events). The TP group was divided into moderate-severe thrombocytopenia (TPmod ; platelet 50–100 × 10 3 μL) and mild thrombocytopenia (TPmild ; platelet 100–150 × 10 3 μL) for further analysis. P -value <0.05 is considered significant. Results: Five hundred and thirty-six patients were identified, and 72 patients (13%) had thrombocytopenia. The median follow-up time was 1.1 years. The TP group was older (TP vs. control: mean age 73 ± 13 years vs. 70 ± 13 years; P = 0.026). In patients discharged on dual-antiplatelet therapy, the TP group had higher all-cause mortality (23% vs. 7.3%; P = 0.007) but not major bleeding events (11% vs. 5.0%; P = 0.123). Only all-cause mortality increased with the severity of thrombocytopenia (TPmod vs. TPmild vs. control: 33% vs. 24% vs. 7.3%; P = 0.007). Conclusions: In patients with ACS, baseline thrombocytopenia is associated with increased all-cause mortality and all bleeding events without net MACE benefit. Further study is needed to identify the optimal antiplatelet strategy in this higher risk population. Highlights: Baseline thrombocytopenia in patients with ACS is associated with all-cause mortality and major bleeding events. Thrombocytopenia should be considered as a surrogate marker of poor prognosis in patients with ACS. In patients with ACS and thrombocytopenia, further study is needed to identify optimal antiplatelet strategies.